Pemberian Mikotricho dan Guano Terhadap Pertumbuhan dan Hasil Tanaman Kacang Tanah (Arachis Hypogaea L.) - Fikrinda, Wahyu; Yeri, Nopenus; Hamzah, Amir (Jurnal Penelitian Pertanian Terapan, 2024)
Micotricho is a technological innovation by utilizing useful microbes in the form of mycorrhizal fungi and trichoderma. Guano is bat manure with the second highest nitrogen content after pigeon droppings, but cow dung ranks first in phosphorus content and third in potassium content. This study aims to determine the effect of a combination of mycotricho (Mycorrhiza and Trichoderma) and guano fertilizer on the growth and yield of peanut plants. This research was conducted in Jetak Ngansri Hamlet, Mulyoagung Village, Dau District, Malang Regency, which was carried out from July - October 2022. This study used a Randomized Block Design (RBD) with 2 treatment factors. The first factor: Dosage of Mikotricho Fertilizer (M) consists of 4 levels, namely: M0 (without Mikotricho), M1 10 (g/plant), M2 (30 g/plant), M3 (50 g/plant). The second factor: Guano Fertilizer (K) consists of 3 levels, namely: K0 (without Guano), K1 (60 g/plant), K2 (120 g/plant). Parameters observed were: plant height, number of leaves, time of flower appearance, number of root nodules/plant, number of pods/plant, fresh pod weight/plant, dry pod weight/plant, dry pod yield, number of seeds/plant, seed weight/ plants, weight of 100 seeds, fresh weight of stover, dry weight of stover and yield. The results of this study indicate that there is an interaction between the application of mycotricho fertilizer (mycorrhiza and trichoderma) and guano fertilizer on the parameters of plant height, number of leaves, time of flower appearance, number of pods, number of active root nodules, wet weight of pods/plant, dry weight of pods/plant, dry pod yield, number of seeds/plant, dry weight of seeds/plant, weight of 100 seeds, fresh weight of stover/plant, dry weight of stover/plant and yield. Interaction combination treatment the best results were obtained in the treatment of guano 60 g/plant and mycorrhiza 30 g/plant with a dry pod yield of 4.14 tons/ha or a seed yield of 2.48 tons/ha.